Study of Shock Ignition Approach in Heavy Ion Fusion of Reactor-size DT Target - s hasani; B kaleji; soheil khoshbinfar (Iranian Journal of Physics Research, 2018)
The ignition of pre-compressed fuel by convergent shock wave, as a new approach in inertial confinement fusion that is known as shock ignition is considered with the aim of achieving high gain and providing threshold of ignition in lower energy. In this research, optimization of the energy of individual ions in the beam according to the hydrodynamic efficiency and target energy gain in a five-layer fuel pellet of nuclear fusion reactor size with heavy ion beam by one-dimensional code, DEIRA4. Then with substitution of the box pulse by three-stage pulse in shock ignition, the power and time of each phase are optimized and the energy consumption, fuel hydrodynamic efficiency and Rayleigh–Taylor instability is investigated. Calculations show that in optimal target with DT fuel, by applying three-stage pulse by heavy ion beam 207Pb, target energy gain is 542 corresponding to 21% increasing in energy efficiency and 19% decreasing in deriver energy. Also the decreasing of implosion velocity and e-fold parameter shows, the hydrodynamic instabilities in shock ignition is less than central ignition.